静电离子加速器装置 (2018)
本发明涉及静电离子加速器装置。种带有阳极辐射冷却的用于静电离子加速器装置的装置，其避免了附加的复杂冷却措施，在该静电离子加速器装置运行期间布置在电离室中的阳极出现不可忽视的热能损耗。 An arrangement with radiation cooling of the anode, which avoids the need for complex additional cooling measures, is proposed for an electrostatic ion accelerator arrangement in which the thermal power loss which is not negligible occurs at the anode, which is arranged in an ionization chamber, during operation.